(untitled) (Itinera, 2022)
This monographic section of “Itinera” develops some of the questions which were raised at the summer school “Aesthetics, Technique and Emotion”, held in June 2020 at the Lake Como School of Advanced Studies (https://aeat.lakecomoschool.org/). The summer school was organized by the University of Milan in collaboration with the European Seminar of Aesthetics (https://sites.unimi.it/eu_aesthetics/). The aim of the school was to investigate the meaning of aesthetics today, in light of the different changes that are occurring in our aesthetic perception of the world. How is technology transforming the way we view the world and art, and what role do emotions still play in this context? What is the value of the performing arts in facing these new challenges, and how is aesthetic experience related to the current issues of morality and politics? These are some of the problems that were raised at the school and this issue seeks to develop them further.